Assessment of knowledge on non-communicable diseases and their screening tests among elderly population in an urban area of Bengaluru - Ramegowda, Chethana; Kathali, Soubhagya; Rajanna, Pushpa (International Journal Of Community Medicine And Public Health, 2019)
Background: Non-communicable diseases (NCDs) are the leading cause of morbidity and premature mortality in most low and middle income countries (LMIC) around the world. Recent estimates shown that about 80% of NCDs deaths occur in LMIC and nearly three fourth of global NCDs related deaths take place after the age of 60. The knowledge of NCDs and their related screening tests among elderly is essential for early detection which reduces further development of the disease and its complications, thereby reducing the burden of health care cost. Hence, the present study was undertaken. Methods: A descriptive study was conducted among 245 study subject after obtaining informed consent. Using pre-tested structured questionnaire, information was collected regarding knowledge on NCDs and their screening tests. Results were entered in Microsoft excel and analyzed using descriptive statistics. Results: 81.6% of study subjects were aware of common NCDs. Off which only 02% were aware of 6 NCDs (out of 12 NCDs considered in this study). Regarding individual diseases, about 61.6% subjects were aware of Hypertension and 52.7% about DM. About knowledge of screening test, 69% were aware about any screening test and 58.8% were aware of screening test for hypertension and 41.6% for diabetes mellitus. Conclusions: The overall knowledge regarding NCDs and their screening tests is poor among elderly population.